Preparing teacher-students for twenty-first-century learning practices (PREP 21): a framework for enhancing collaborative problem-solving and strategic learning skills. Issue 1 (2nd January 2017) - Häkkinen, Päivi; Järvelä, Sanna; Mäkitalo-Siegl, Kati; Ahonen, Arto; Näykki, Piia; Valtonen, Teemu
Abstract: With regard to the growing interest in developing teacher education to match the twenty-first-century skills, while many assumptions have been made, there has been less theoretical elaboration and empirical research on this topic. The aim of this article is to present our pedagogical framework for the twenty-first-century learning practices in teacher education. We will first review the current status of policy frameworks for the twenty-first-century learning skills. Based on our previous work and current understanding in the field of learning sciences, we will next elaborate the processes and strategies for collaborative problem-solving skills and strategic learning skills to specify current, rather general claims presented regarding the discussion on twenty-first-century skills. We will also provide concrete case examples facilitating strategic learning skills, collaborative problem-solving skills, and the skills to use information and communication technologies in contexts of our previous studies.